Stakeholders, reward expectations and firms' use of the ISO14001 management standard. Issue 7 (1st July 2014) - Simpson, Dayna; Sroufe, Robert
Abstract : Purpose: – An ongoing challenge for managers is to define and benefit from their firm's environmental management practices. Firms that seek stakeholder recognition of their practices, or face stakeholder pressure for evidence of improvement, increasingly use management standards such as ISO14001. Such standards, however, may encourage firms to use more reportable rather than embedded environmental management practices. Why some firms use environmental management standards to improve practices relative to firms that use them to deflect attention, is an important research question. As paper proposes, stakeholder pressure on firms for improved practices can interact with firms' expectations of related rewards to influence environmental management outcomes. The paper aims to discuss these issues. Design/methodology/approach: – The intention was to identify significant differences in stakeholder focus and each firm's environmental management practices, between ISO14001 certified and non-certified firms. The paper explored the propositions with a sample of US manufacturers. The paper used a PLS modeling approach. Findings: – The paper identified links between firms with a greater regulative stakeholder focus, to greater use of reportable practices (pollution reduction). Firms with a greater normative stakeholder focus were linked to greater use of embedded practices (policies and pollution prevention). Originality/value: – This study is one of the first to assess differences that distinguish between both stakeholder type and choice of environmental management practices. Further, the paper grouped firms' practices according to their emphasis on either rewards of stakeholder recognition or internal operational benefit. As other studies have identified, firms do not necessarily adopt environmental management standards for their goals of practice improvement. The study contributes to use of stakeholder theories to understand firm level adoption of and benefit from environmental management practices.